Daphnetin: A bioactive natural coumarin with diverse therapeutic potentials - Javed, Maira; Saleem, Ammara; Xaveria, Anne; Akhtar, Muhammad Furqan (Frontiers in Pharmacology, 2022)
Daphnetin (DAP), a coumarin derivative extracted from Daphne species, is biologically active phytochemical with copious bioactivities including anti-inflammatory, anti-oxidant, neuroprotective, analgesic, antipyretic, antimalarial, anti-bacterial, anti-arthritic, neuroprotective, hepatoprotective, nephroprotective and, anti-cancer activities. It is reported to interact with multiple cellular mediators and signaling pathways to provide protection against neurodegeneration and arthritis. This review focuses on sources, synthesis, structure activity relationship, and various bioactivities of DAP. Neuroprotective and anti-inflammatory action of DAP is additionally aided by its modulation of the JNK-MAPK, JAK-STAT, and TLR-4/NF-κB signaling pathways. Although, the part of its anti-arthritic effect is mediated through immunoregulation, antioxidant and anti-inflammatory actions via regulation of NF-κB, MAPK and MMP signaling pathways, the anticancer action of DAP is mediated due to inhibition of Akt/ NF-Kb, MAPK signaling pathways, and the activation of Keap1-Nrf2 pathway. It is devoid of any organ toxicity and mortality as well as mutagenicity, mucosal irritation and sensitization reactions. Based on a review of the literature, DAP has a promising pharmacological and safety profiles and can be employed as a pharmaceutical moiety to treat a variety of illnesses. The current review intends to provide an in-depth focus on pharmacological activity and phytoanalytical approaches of DAP.